Endometrial Carcinoma Presenting as Vasculitic Sensorimotor Polyneuropathy - Marketa Vasku; Thomas Papathemelis; Nicolai Maass; Ivo Meinhold-Heerlein; Dirk Bauerschlag (Hindawi Limited, 2011)
Paraneoplastic syndromes (PNS) are a heterogeneous group of symptoms which are indirectly caused by primary or metastatic tumor. Paraneoplastic polyneuropathy (PNP) is mostly related to small cell lung cancer (5%), prostate, gastric, and breast cancer. Only sporadic cases have been reported to be associated with endometrial cancer. We present a case of a premenopausal woman with severe vasculitic, asymmetric sensorimotor polyneuropathy that developed in conjunction with an endometrial carcinoma responding to surgical therapy of primary tumor combined to steroid therapy. Neurological symptoms such as asymmetrical sensorimotor deficits and painful paresthesias are suspicious when they occur in otherwise healthy women with no medical history. The phenomenon of a paraneoplastic syndrome can point to an underlying malignancy and can be used as marker of progression or regression of the tumor. Due to the rarity of PNP, there is no standard treatment. Recommended therapy is stage-adjusted treatment of the primary tumor.